Asexuality and epistemic injustice: a gendered perspective - Cuthbert, Karen (Journal of Gender Studies, 2022)
Drawing on original qualitative research, I argue that the concept of ‘epistemic injustice’ proposed by the feminist philosopher Miranda Fricker, and located within a long genealogy of Black feminist scholarship, can be used sociologically to help understand the lived experiences of asexual people. I show how participants’ accounts of their asexual subjectivities were frequently denied, dismissed and over-written. However, I argue that these experiences were heavily gendered, in that asexual women were subject to epistemic injustices to a degree and in ways that their male counterparts were not, and that this must be understood within the power relations of hetero-patriarchy. These epistemic injustices revolved around old yet prevailing constructions of femininity and womanhood as ‘naturally’ asexual, passive, and lacking agency. When asexual men experienced epistemic injustice, this was rooted in familiar understandings of masculinity as necessitating an active and desiring sexuality. Using Fricker’s elucidation of hermeneutical and testimonial forms of epistemic injustice, I show how asexuality remains a culturally unfamiliar hermeneutical frame in a context of ‘compulsory sexuality’ but also how stories of asexuality are ‘heard’ based on the gendered (and unequal) distribution of testimonial credibility.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asexualité; cours; cycles supérieurs; discipline; europe; fem9000; injustices épistémiques; patriarcat; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; violences; études de genres

#MeToo and testimonial injustice: An investigation of moral and conceptual knowledge - Hänel, Hilkje C (Philosophy & Social Criticism, 2022)
Two decades ago, Tarana Burke started using the phrase ‘me too’ to release victims of sexual abuse and rape from their shame and to empower girls from minority communities. In 2017, actress Alyssa Milano made the hashtag #MeToo go viral. This article’s concern is with the role of testimonial practices in the context of sexual violence. While many feminists have claimed that the word of those who claim to being sexually violated by others (should) have political and/or epistemic priority, others have failed to recognize the harm and injury of instances of sexual violence that are not yet acknowledged as such and failed to listen to victims from marginalized social groups. In fact, some feminists have attacked #MeToo for mingling accounts of ‘proper’ sexual violence and accounts that are not ‘proper’ experiences of sexual violence. My aim in this article is to show why this critique is problematic and find a philosophically fruitful way to understand the #MeToo-movement as a movement that strives for moral and conceptual progress.
Keywords: #metoo; approches et analyses; cours; cycles supérieurs; discipline; fem9000; justice sociale; patriarcat; philosophie; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; violences sexuelles

Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

La puissance féministe - Gago, Verónica (Éditions de la rue Dorion, 2021)
L’Amérique du Sud est un des coeurs battants du féminisme contemporain. Des millions de femmes y prennent la rue contre les féminicides, les violences qui frappent les minorités de race et de genre, les lois qui répriment l’avortement et le développement néo-extractiviste. Figure majeure du féminisme latino-américain, Verónica Gago réinscrit ces bouleversements dans l’émergence d’une internationale féministe et propose, avec La puissance féministe, un antidote à tous les discours de culpabilité et de victimisation. En se réappropriant l’arme classique de la grève, en construisant un féminisme populaire, radical et inclusif, les mouvements sud-américains ont initié une véritable révolution. C’est à partir de l’expérience de ces luttes que Gago reconceptualise la question du travail domestique et de la reproduction sociale, expose les limites du populisme de gauche et dialogue avec Spinoza, Marx, Luxemburg ou Federici. Parce qu’il unit la verve politique du manifeste aux ambitions conceptuelles de la théorie, La puissance féministe est un livre majeur pour saisir la portée internationale du féminisme aujourd’hui.
Keywords: 2000 à aujourd'hui; amérique latine; amériques; approches et analyses; care; cours; cycles supérieurs; fem7000; histoire et politique; justice sociale; militance; patriarcat; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; violences

Hermeneutical Backlash: Trans Youth Panics as Epistemic Injustice - George, B. R.; Goguen, Stacey (Feminist Philosophy Quarterly, 2021)
In this paper we use the contemporary example of trans youth panics to introduce the notion of hermeneutical backlash, in which defenders of an established, unjust hermeneutical regime actively work to undermine and discredit hermeneutical liberation. We argue that the strategies and tropes of the trans youth panic illustrate a general propaganda vulnerability of epistemic liberation movements (including familiar examples from recent history), and so are troubling for reasons that go beyond their application to trans youth. This exploration of a few specific cases of hermeneutical liberation and hermeneutical backlash calls attention to the need for further theoretical work on the dynamics of struggles for (and against) hermeneutical justice.
Keywords: approches et analyses; backlash herméneutique; cours; cycles supérieurs; discipline; discours dominant; discours médiatique; enfants trans*; fem9000; histoire et politique; hétérosexisme; injustices herméneutiques; militance; philosophie; philosophie féministe; sciences humaines; systèmes d'oppressions; thématiques; transphobie; violences

Applied epistemology - Lackey, Jennifer (Engaging philosophy, 2021)
Leading philosophers bring the tools of contemporary epistemology to bear on some of the most pressing social and political questions facing us as agents in the world today. This volume explores a diverse range of topics as they relate to epistemology under broad themes including injustice, race, feminism, sexual consent, and the internet.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; histoire et politique; injustice; justice sociale; philosophie; sciences humaines; thématiques; violences; épistémologie; éthique

Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge studies in contemporary philosophy, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"-- Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Epistemic Decolonization as Overcoming the Hermeneutical Injustice of Eurocentrism - Posholi, Lerato (Philosophical Papers, 2020)
This paper is broadly concerned with the question of what epistemic decolonization might involve. It is divided into two parts. The first part begins by explaining the specifically epistemic problem to which calls for epistemic decolonization respond. I suggest that calls for decolonization are motivated by a perceived epistemic crisis consisting in the inadequacy of the dominant Eurocentric paradigm to properly theorize our modern world. I then discuss two general proposals, radical and moderate, for what epistemic decolonization might involve. In the second part, I argue that the inadequacy of Eurocentric epistemic resources constitutes a hermeneutical injustice caused by an irreducible form of epistemic oppression. I then argue that addressing this form of epistemic oppression requires thinking ‘outside’ of the Eurocentric paradigm because the paradigm might fail to reveal and address the epistemic oppression sustaining it. This lends further plausibility to the radical proposal that epistemic decolonization must involve thinking from ‘outside’ the Eurocentric paradigm, but also accommodates the moderate proposal that adopting critical perspectives on Eurocentric thought is an important part of epistemic decolonization.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; décolonisation épistémique; fem9000; féminisme décolonial; injustices herméneutiques; injustices épistémiques; philosophie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

Je suis un monstre qui vous parle: rapport pour une académie de psychanalystes - Preciado, Paul B. (Grasset, 2020)
« La psychanalyse est face à un choix historique sans précédent : soit elle continue à travailler avec l'ancienne épistémologie de la différence sexuelle et légitime de facto le régime patriarco-colonial qui la soutient, devenant ainsi responsable des violences qu'elle produit, soit elle s'ouvre à un processus de critique politique de ses discours et de ses pratiques. Continuer à pratiquer la psychanalyse en utilisant la notion de différence sexuelle, avec des instruments cliniques comme le complexe d'OEdipe, est aussi aberrant que de prétendre la terre plate. Le temps est venu de sortir les divans sur les places, collectiviser la parole, politiser les corps, débinariser la sexualité et décoloniser l'inconscient : la survie de la psychanalyse est à ce prix. »-- Quatrième de couverture.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; discours dominant; fem7000; identités LGBTQIA2+; patriarcat; personnes trans*; sciences humaines; systèmes d'oppressions; thématiques; violences; épistémologie